2018
DOI: 10.1016/j.japh.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delayed prescription fill on readmission rates for chronic obstructive pulmonary disease and heart failure

Abstract: Delaying discharge prescription fills resulted in a nonsignificant increase in the rate of HF readmission but did not increase the rate of readmission for COPD. Rate of delaying prescription fill was not statistically greater for any of the baseline characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This is particularly important because delayed prescription filling of HF medications has been associated with an increase in hospital admissions, and multiple studies have identified cost as a reason for sacubitril/valsartan discontinuation. 13,15,54…”
Section: Cost/accessmentioning
confidence: 99%
“…This is particularly important because delayed prescription filling of HF medications has been associated with an increase in hospital admissions, and multiple studies have identified cost as a reason for sacubitril/valsartan discontinuation. 13,15,54…”
Section: Cost/accessmentioning
confidence: 99%